News Framing on Actors of National Capital City (IKN) Through Cultural Communication of `Tanah’ and `Air’ Unity in Online Media - ., Dwinarko; Yasya, Wichitra; Widodo, Aan (KnE Social Sciences, 2023)
Against the backdrop of historical communicative actions, the news is the outcome of knowledge in the reality of everyday life. The homo sociological communication model consists of behaviors that refer to collective norms and values, especially laws that declare a requirement, a social order which is then ensured by normative conventions. Through actors and cultural symbols, social action, transcendence, and objectivity become communication acts in the form of news framing. The State Capital or Ibu Kota Negara (IKN) has been the subject of news in the media. This study then aimed to determine news context on the unity of land and water (Tanah dan Air) as a metaphor for the State Capital’s relocation from Jakarta to East Kalimantan Alfred Schutz’s Communicative Action theory. The research used qualitative methodology, while analysis was done using narrative analysis. The findings of this research are the symbols of land and water in the discourse of framing the news of the transfer of the State Capital (IKN) since the administrations of President Sukarno to President Jokowi became a reality of communicative acts with historical significance and cultural communication through land and water rituals. The discourse frame is a value that contributes to profound political and cultural dialogue and equal growth. Sociologically, communicative behavior in new framing results from integrating players historical, cultural, and political interests. Based on the research findings, the recommendation put forward is policy analysis on the transfer of IKN, which must continue to investigate history via cultural communication and social action of players on homo sociologicus and history who possess strategic collective values and norms for sustainable cultural and economic development. Keywords: news framing, communicative action theory, cultural communication